REPRESENTASI ALTURISME PADA TOKOH KIAI MOKO DALAM LEGENDA “API TAK KUNJUNG PADAM” DARI PAMEKASAN - Arief Setyawan; Khusnul Khotimah; Albitar Septian Syarifudin; Fiyan Ilman Faqih (UNIVERSITAS PGRI YOGYAKARTA, 2025)
This study discusses the altruistic behavior of the character Kiai Moko in “Legenda Api Tak Kunjung Padam” (The Legend of the Never-Ending Fire) set in the Pamekasan Regency using a qualitative descriptive method. The purpose of this study is to describe the altruism of the character Kiai Moko based on Einsberg dan Mussen' theory of altruism. Data collection techniques used literature review, reading, and note-taking. Meanwhile, the data analysis techniques used included data reduction, data presentation, and conclusion drawing. Based on the study, it was found that the character Kiai Moko represented altruistic behavior in the storyline. This behavior was manifested through three aspects, namely paying attention, helping others, and putting others first. These findings show that Kiai Moko, as one of the legendary figures in Pamekasan, represents an altruistic character that reflects a personality worthy of emulation and should be passed down from generation to generation as a means of character education. In addition, this reflection can also be used as a characteristic of the identity of the people of Pamekasan.